Charge states of strongly correlated 3d oxides: from typical insulator to unconventional electron-hole Bose liquid: Новые электронные материалы и системы - Moskvin, A.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We present a model approach to describe charge fluctuations and different charge phases in strongly correlated 3d oxides. As a generic model system one considers that of centers each with three possible valence states M0,± described in frames of S = 1 pseudospin (isospin) formalism by an effective anisotropic non-Heisenberg Hamiltonian which includes both two types of single particle correlated hopping and the two-particle hopping. Simple uniform mean-field phases include an insulating monovalent M0 phase, mixed-alence binary (disproportionated) M± phase, and mixed-valence ternary («under- disproportionated») M0,± phase. We consider two first phases inmore details focusing on the problem of electron-hole states and different types of excitons in M0 phase and formation of electron-hole Bose liquid in M± phase. Pseudospin formalism provides a useful framework for revealing and describing different topological charge fluctuations, in particular, like domain walls or bubble domains in antiferromagnets. Electron-lattice polarization effectsare shown to be crucial for the stabilization of either phase. All the insulating systems such as M0 phase are subdivided to two classes: stable and unstable ones with regard to the formation of self-trapped charge transfer (CT) excitons. The latter systems appear to be unstable with regard to the formation of CT exciton clusters, or droplets of the electron-hole Bose liquid. The model approachsuggested is believed to be applied to describe a physics of strongly correlated oxides such as cuprates, manganites, bismuthates, and other systems with charge transfer excitonic instability and/or mixed valence. We shortly discuss an unconventional scenario of the essential physics of cuprates which implies their instability with regard to the self-trapping of charge transfer excitons and the formation of electron-hole Bose liquid.